Enhanced flow boiling heat transfer with fractal-like geometrical structures fabricated by additive manufacturing - See, Yao Song (Nanyang Technological University, 2020)
Due to the increasing needs in thermal management, two-phase cooling schemes have been implemented to address the high power densities in computing devices. In recent years, flow boiling as a means of heat removal, together with the use of straight minichannels and microchannel heat sinks have gained significant research interest. The issue with these heat sink designs, however, is that flow instabilities occur. This leads to geometrical modifications in order to minimise these flow instabilities. Fractal-like minichannels have been shown to be able to reduce flow instabilities while enhancing heat transfer and reducing pressure drop over its parallel counterparts. The objective of this thesis is to evaluate the potential enhancement of heat transfer in fractal-like channels over conventional parallel channels. Both heat transfer and pressure drop performances were evaluated using a closed-loop two-phase experimental facility. The fluid used is FC-72, a dielectric fluid which is chemically inert and ideal for electronic applications. Both symmetrical and asymmetrical fractal-like channels were fabricated together with a conventional parallel design to be investigated. The results show enhanced heat transfer in the fractal-like channels over the parallel channels, even though the pressure drops are comparable, with the asymmetrical design having a slightly lower pressure drop at high heat fluxes. It was also found that the diverging flow prevents flow instabilities while the converging flow causes temporal vapour bubble build-up. Three diameter ratios were selected; each diameter ratio being previously derived to be optimal under single-phase conditions, and four branch levels ranging from 1 to 4 were selected. Results show that all fractal-like channels demonstrate enhanced heat transfer and lower pressure drop over the parallel channels, especially at higher mass fluxes. The fractal-like channels also exhibit convective-dominant heat transfer. Visualisation studies show that flow instabilities are rate in fractal-like channels, even though at high branch levels, there are cases of temporal vapour bubble build-up which could be due to the higher number of bifurcations that contribute to the increase in pressure drop. Both two-phase heat transfer coefficient and pressure drop correlations for the fractal-like channels were developed. The entropy generation of a single channel and a fractal-like channel were also investigated. A simple total rate of entropy generation equation was developed for symmetrical and dichotomous fractal-like channels, and used to evaluate its rate of entropy generation. It was shown that the rate of entropy generation in fractal-like channels are lower than the conventional parallel design, suggesting a more efficient utilisation of exergy. An analysis of the entropy generation also shows that the higher branch levels are not ideal for flow boiling applications as compared to the lower branch levels, and that diameter ratios certainly contribute to the rate of entropy generation. Finally, optimised ranges of diameter ratios under flow boiling for symmetrical and dichotomous fractal-like channels were proposed that achieved the lowest rate of entropy generation.